Childhood heart disease and parental emotional wellbeing: a predictive model to explain the perception of quality of life in children and adolescents - Teresa Grimaldi Capitello; Cinzia Correale; Giulia Amodeo; Michela Balsamo; Leonardo Carlucci; Caterina Fiorilli (Health and Quality of Life Outcomes)
Abstract Background The number of people living with congenital heart disease (CHD) in 2017 was estimated to be 12 million, which was 19% higher than that in 1990. However, their death rate declined by 35%, emphasizing the importance of monitoring their quality of life due to its impact on several patient outcomes. The main objective of this study is to analyze how parents’ psychosocial factors contribute to children’s and adolescents’ perceptions of their QoL, focusing on their medical condition. More specifically, we explore how parental psychological dimensions, such as anxiety and depression, are related to patients’ health-related quality of life (HRQoL). Methods We recruited 447 children aged 5 to 18 years with a CHD diagnosis and their parents (319 mothers and 229 fathers) from January to December 2018. Patients were referred to the Cardiology Department of “Bambino Gesù” Children’s Hospital and participated in multidisciplinary standardized follow-up. Children and adolescents were submitted to a comprehensive evaluation by different physicians, including pediatric cardiologists, surgeons, and psychologists, at preset time frames. A series of standardized questionnaires were administered during psychological assessment. Results The main findings show a negative correlation between mothers’ anxiety and three patients’ HRQoL subscales (Treatment II, Treatment anxiety, and Communication). Similarly, mothers’ depression correlates negatively with other patients’ HRQoL subscales (heart problems, symptoms, perceived physical appearance, cognitive problems, and communication). Fathers’ anxiety and depression show negative correlations with only the subscale of Treatment II. More generally, the perceived quality of life of children and adolescents with CHD is influenced by their medical conditions as well as the parents’ psychological dimensions. Conclusions Our findings suggest that the caregivers of pediatric patients with CHD are more exposed to psychological problems of anxiety and depression, which affect the perceived quality of life of their children. Longitudinal research with a healthy control group is recommended to further consolidate this evidence.